Effect of bokashi organic fertilizers on the lettuce plants (Lactuca sativa) growth in the Southern Campanha Gaúcha Region - Hanke, Daniel; Silva Nascimento, Shirley Grazieli da; Moura, Thaís Teixeira; Maia, Joélio Farias; Becker, Cláudio; Murata, Afonso Takao (Revista Ambientale, 2025)
The application of Bokashi can enhance nutrient use efficiency in vegetable crops, reducing reliance on mineral fertilizers. This study aimed to evaluate the effects of aerobic and anaerobic Bokashi fertilizers on the development of lettuce (Lactuca sativa), as well as on soil and substrate attributes, in comparison with conventional mineral fertilization (NPK). Two experiments were conducted (in soil and in sand-based substrate) using a randomized block design with the following treatments: Control (no fertilization); T1 = 100% of the recommended NPK dose; T2 = Aerobic Bokashi; T3 = Anaerobic Bokashi; T4 = 50% Aerobic Bokashi + 50% NPK; and T5 = 50% Anaerobic Bokashi + 50% NPK. Plants were grown for 63 days, and both shoots and roots were evaluated. After harvest, soil and substrate samples were also analyzed. Data were subjected to ANOVA followed by Tukey’s test (p < 0.05). Results demonstrated that: (i) Bokashi fertilizers promoted greater lettuce development compared to conventional mineral fertilization (NPK); (ii) the positive effect of Bokashi was more pronounced in the sand-based substrate than in soil; and (iii) the most responsive variables to Bokashi treatments were fresh and dry biomass (shoots and roots), root length, and shoot height.